Mr. Holmes [videorecording (DVD)] - McKellen, Ian; Linney, Laura; Parker, Milo; Sanada, Hiroyuki, 1960-; Cullin, Mitch, 1968- (Lionsgate, 2015)
In 1947, an aging Sherlock Holmes returns from a journey to Japan, where, in search of a rare plant with powerful restorative qualities, he has witnessed the devastation of nuclear warfare. Now, in his remote seaside farmhouse, Holmes faces the end of his days, with only the company of his housekeeper and her young son, Roger. Grappling with the diminishing powers of his mind, Holmes comes to rely upon the boy as he revisits the circumstances of the unsolved case that forced him into retirement.